Animal models of acute gastric mucosal injury: Macroscopic and microscopic evaluation. Issue 2 (5th April 2019) - Simões, Sandra; Lopes, Rui; Campos, Maria Celeste Dias; Marruz, Maria João; da Cruz, Maria Eugénia Meirinhos; Corvo, Luísa
Abstract: Acute gastric mucosal injury is a common disorder of the gastrointestinal tract and the search for new therapeutics is ongoing. The aim of this study is to update and expand the information related to the most widely used rat models of acute gastric ulcer, the ethanol‐induced ulcer and the indomethacin‐induced ulcer. These two models are compared in terms of macroscopic and microscopic features. Experimentally, ethanol was given orally in a single dose and indomethacin was subcutaneously injected into male Wistar rats. After ulcerative challenges, the stomachs were removed and visually inspected. Anti‐ulcerative drugs were used to validate the models. Histological analysis of the stomachs determined the microscopic score. The methodology used for model evaluation applied to macroscopic and microscopic gastric lesions. With these methods it was possible to induce lesions in the gastric mucosa. Microscopic evaluation permitted assessment of the inflammatory and apoptotic impact in the mucosa not observable by macroscopic evaluation. Groups of animals were treated with two standard drugs: sulcralfate suspension or lansoprazole solution. Both drugs reduced macroscopic and microscopic lesions, particularly the hemorrhagic ones. Both models induced acute gastric mucosal injury and no single evaluation method can address all the aspects of the pathology of gastric lesions. As a complement to macroscopic evaluation, microscopy appears to be a relevant tool to selectively identify specific aspects of the development of mucosal injury, quantify the extent of lesions, and contribute to an appropriate interpretation of results. The score systems established here offer a reliable method for testing antiulcer drugs.